PENGARUH BAURAN PEMASARAN 7 P TERHADAP KEPUTUSAN PEMBELIAN (PEMAKAI JASA) GADAI DI PEGADAIAN CPP PURWOTOMO SURAKARTA - Sarjana Rini, Luluk Takari; Ningrum, Retno; Resihono, Legowo Dwi; Hardiyansyah, Dito Wahyu (Universitas Of Surakarta, 2024)
This study aims to determine the effect of the 7P marketing mix either partially or simultaneously on the puchase decision (use of service) of pawns at PT Pegadaian CPP Purwotomo Surakarta. This type of research is quantitative research. With the sampling technique using simple random sampling. The sample in this study amounted to 103 customers of PT. Pegadaian CPP Purwotomo Surakarta. The data collection technique uses a questionnaire that is processed using SPSS 19. The results of this study indicate that the 7P marketing mix variables do not all have a positive effect on purchasing decisions (use of services) pawns at PT. Pegadaian CPP Purwotomo Surakarta. The data analysis used is validity test, reliability test, classical assumption test, multiple linier regression test, hypothesis test, and coefficient of determination. The results of this study indicatet that the product (X1), Price (X2), Place (X3), People (X5), Process (X6), and Physical evidence (X7) have no effect on purchasing decisions (use of services) pawns at PT. Pegadaian CPP Purwotomo Surakarta. Promotion (X4) has an effect on purchasing decisions (use of services) pawns. The seven P’s of marketing mix variables simultaneously influence purchasing decisions (use of services) pawns at PT. Pegadaian CPP Purwotomo Surakarta.